The Influence of Staff Compensation on Employee Turnover Intention in Food and Beverage Industry in Nigeria - Chukwu, B.A; Ezeabogu, A.N; Aguwamba, S.M (International Journal of Economics, Business and Management Studies, 2019)
This research examined the influence of staff compensation on employees turnover intention in food and beverage industry in Nigeria. Labour turnover costs food and beverage industry huge sum of money annually in hiring and training replacements. Retention of employee is not easy and is a complex issue and there is no single recipe for retaining employees in the company. Management of food and beverage industry can reduce turnover by considering different preventive measures such as regular and adequate compensation comparable to labour market rate. Employees will opt out of the organization if they are not paid labour market rate of compensation. This study adopted a survey research instrument through administration of questionnaire. The data for the research were analyzed using descriptive statistics and chi-square. The empirical results from the chi-square analysis showed that adequate compensation, binding pay with performance, payment of labour market rate and when pay is commensurate with input and experience has significant influence on employee turnover intention at 5 percent level of significance. Based on the research findings, it is recommended that employees should be paid adequate compensation in line with labour market rate and not what the corporate guideline dictates.